Regard sur la norme endogène du français en Côte d’Ivoire - Affoué Cécile N’guessan (Anadiss, 2014)
This article discusses the issue of endogenous standard French in Côte d’Ivoire. The text shows that the ownership of the French, much more widespread among the population, tends to establish an endogenous standard in the country. This is favored by the sociolinguistic context of Côte d’Ivoire where French coexists with sixty local languages more or less widely, none of which is clearly dominant. There is also the language policy of the country largely in favor of French appreciably influence the attitude of Ivorians vis-à-vis the language.